2020
DOI: 10.1021/acsaem.0c01723
|View full text |Cite
|
Sign up to set email alerts
|

Melt Spinning of Low-Cost Activated Carbon Fiber with a Tunable Pore Structure for High-Performance Flexible Supercapacitors

Abstract: Activated carbon fibers are emerging as one of the most promising electrode for flexible supercapacitors, as they are highly conductive, lightweight, and flexible. However, the high preparation cost and unreasonable pore structure limit their practical application in supercapacitors. Here, we developed a cost effective and green method to fabricate activated carbon fiber with a controllable porous structure by employing Kraft hardwood lignin extracted from black liquor of papermaking as raw material and nano-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…Figure 5g shows a comparison of the specific capacitance of the supercapacitor in this study and recently reported FSSCs based on carbon-based fiber electrodes. The specific capacitance reported in this work is larger than many previously reported FSSCs, including supercapacitors based on ACF (54.2 at 0.2 A g −1 ), 55 MnO 2 /CNTF (17.1 at 1 A g −1 ), 56 Mn 3 O 4 and MoS 2 /CF (70 at 0.5 A g −1 ), 57 NCHrGO/ CF//NQrGO/CF (69.1 at 0.41 A g −1 ), 58 MWCNT/MOF (151.1 at 1 A g −1 ), 2 CF/CNT/MnO 2 //CF/CNT/PPy (59.7 at 0.5 A g −1 ), 24 and FHRCF (122.2 at 1 A g −1 ). 59 As shown in Figure 5h, the Ragone plot of the PPy VANA/ CNTF-based FSSC is compared with the counterpart based on the carbon-based fiber reported recently.…”
Section: Resultscontrasting
confidence: 65%
“…Figure 5g shows a comparison of the specific capacitance of the supercapacitor in this study and recently reported FSSCs based on carbon-based fiber electrodes. The specific capacitance reported in this work is larger than many previously reported FSSCs, including supercapacitors based on ACF (54.2 at 0.2 A g −1 ), 55 MnO 2 /CNTF (17.1 at 1 A g −1 ), 56 Mn 3 O 4 and MoS 2 /CF (70 at 0.5 A g −1 ), 57 NCHrGO/ CF//NQrGO/CF (69.1 at 0.41 A g −1 ), 58 MWCNT/MOF (151.1 at 1 A g −1 ), 2 CF/CNT/MnO 2 //CF/CNT/PPy (59.7 at 0.5 A g −1 ), 24 and FHRCF (122.2 at 1 A g −1 ). 59 As shown in Figure 5h, the Ragone plot of the PPy VANA/ CNTF-based FSSC is compared with the counterpart based on the carbon-based fiber reported recently.…”
Section: Resultscontrasting
confidence: 65%
“…105,106 Fibers with different diameters and/or hierarchical structures are apt to be made from a single or multiple materials by tuning initial processing parameters. General spinning techniques such as wet spinning, 107 dry spinning, 108 melt spinning, 109 electrospinning 110 and centrifugal spinning 111 have all been applied to fabricate fibers or yarns using various materials. In addition, thermal drawing is a facile and scalable approach to producing fibers and has been employed to fabricate smart textiles.…”
Section: Essential Features Of the 1d Conductormentioning
confidence: 99%
“…Spinning can produce or functionalize continuous fibers, which has been realized for mass production. , Fibers with different diameters and/or hierarchical structures are apt to be made from a single or multiple materials by tuning initial processing parameters. General spinning techniques such as wet spinning, dry spinning, melt spinning, electrospinning and centrifugal spinning have all been applied to fabricate fibers or yarns using various materials. In addition, thermal drawing is a facile and scalable approach to producing fibers and has been employed to fabricate smart textiles. This approach enables the targeted materials to be filled into a prepared “preform” and allows simultaneous extrusion of various functional materials within a one-body design.…”
Section: Essential Features Of the 1d Conductormentioning
confidence: 99%
“…As one of the most prospective energy supply systems, SCs can present high power density, low cost, and admirable electrochemical stability. Particularly, fiber-based SCs are more suitable for portable and wearable electronics due to their distinctive capability to keep steady high performance under severe mechanical deformation. However, fiber-based SCs suffer from insufficient energy density, which hampers their applications in the field of energy storage . Enhancing the energy density of fiber-based SCs is of great significance for trendy flexible energy storage devices .…”
Section: Introductionmentioning
confidence: 99%